A degraded adhesion model for creep force calculation based on the CONTACT algorithm. (July 2023) - Shi, Zhiyong; Meacci, Martina; Porcelli, Margherita; Meli, Enrico; Rindi, Andrea
Degraded adhesion is observed extensively during the braking or traction process. An accurate degraded adhesion law, on the other hand, is difficult to acquire since it is characterized by a complicated non-linear behaviour involving various surface phenomena. This work provides a new local degraded adhesion model, its implementation in a wheel-rail contact model, and its application in a multibody railway vehicle model. The present degraded adhesion model takes into account large sliding and adhesion recovery phenomena, which are strictly related to the power dissipated at the contact interface. Implementation of the current local degraded adhesion model enhances Kalker's CONTACT algorithm. The application into multibody dynamics simulation demonstrates the high accuracy of computations. The model is validated by comparing it to experimental findings obtained from on-field tests. Simulated results regarding the tangential pressures, the slip velocity, and the dissipated power under degraded adhesion and partial adherence conditions are reported.